Calculation Method of River Width of Mountainous Watershed Based on Watershed Morphology - LI Qian (Renmin Zhujiang)
The calculation of river floods in mountainous and hilly areas is crucial for mountain flood prevention and forecasting.However,how to calculate accurately the river width in the mountainous and hilly areas has become a key issue in the calculation of mountain floods.This paper takes the modified river development coefficient Kw which reflects the watershed morphology as a selection indicator for the best generalized formula for river width,and proposes a river width calculation method based on watershed area and river development coefficient by analyzing the measured section data of the rivers of 6 mountainous watersheds in 2 provinces.After being verified in Beizhangdian Watershed in Shanxi Province and Qingshuizhan Watershed in Hunan Province,the results indicate that the accuracy of this calculation method for river width is better,which can provide the calculation support for mountain flood forecast.